Plantas para cobertura do solo e estratégias de amostragem sob a ótica do controle biológico conservativo - Oliveira, Pablo Garcia de (2023)
Knowing the arthropod fauna associated with entomophilous plants and to the soil cultivated with same, as well as understanding the influence of pan trap colors and heights on arthropod sampling are crucial to the development of conservative biological control programs. Thus, the second chapter of this thesis verified whether crop succession affects the soil associated epiedaphic arthropod fauna. Was collected arthropods present in soil cultivated with pasture (Brachiaria decumbens) and in soil cultivated with green manures (sunn hemp Crotalaria juncea, pigeon pea Cajanus cajan, jack bean Canavalia ensiformis and gray velvet bean Mucuna pruriens). A significant difference was observed for the abundance, richness and diversity among the arthropod fauna of the soil, obtaining higher averages of abundance and richness in soil cultivated with pasture, while higher diversity value was found in soil cultivated with green manures. There was a significant difference for the means of abundance and richness of detritivores, phytophagous, parasitoids and predators associated with the soil cultivated with pasture and the soil cultivated with green manures. The third and fourth chapters mainly investigated the potential of C. juncea, C. ensiformis, C. cajan, M. pruriens and the soil cultivated with such plants in attracting natural enemies, phytophagous and pollinators. The highest averages of abundance and richness of parasitoids/m2 were obtained in gray velvet bean, while the highest averages of abundance and richness of predators/m2 were obtained in jack bean plants. As for phytophagous and pollinators, sunn hemp exhibited the highest averages abundance/m2. It found higher averages of abundance and richness of phytophagous, parasitoids and predators/m2 in the soil cultivated with sunn hemp and in the soil cultivated with jack bean. The fifth chapter evaluated the efficiency of colors (yellow, blue and transparent) of pan traps in sampling insects associated with the aforementioned green manure plants. For abundance and diversity, there was a significant difference between yellow, blue and transparent pan traps. The abundance and richness of the orders Coleoptera, Diptera, Hemiptera and Hymenoptera were significantly higher in yellow pan trap, however for Thysanoptera such indices did not differ significantly between yellow and blue pan traps. The abundances and riches of parasitoids and predators, as well as the richness of phytophagous and the abundance of pollinators, were significantly higher in yellow pan trap. Finally, the sixth chapter investigated the influence of the height (0.8 and 1.8 m) of yellow pan traps on the sampling of insects associated with C. juncea plants. Insect richness and diversity were significantly higher in yellow pan traps at 0.8 m. The abundance and richness of parasitoids and pollinators were significantly different between yellow pan traps at 0.8 m and yellow pan traps at 1.8 m. Phytophages were significantly more abundant in yellow pan traps at 1.8 m. It was concluded that changes in soil cover affect the composition of the epiedaphic arthropod fauna associated with same; green manures attract and conserve natural enemies and pollinators; the color and height of the trap influence the capture of insects.